Analysis of probe excited circular ring above reflector in outdoor WLAN systems - Phongcharoenpanich, Chuwong; Chawanonphithak, Yuktitath; Wounchoum, Phairote; Krairiksh, Monai (My University, 2005)
This paper presents the analysis of probe excited circular ring above reflector in WLAN bridge systems. The evaluation performance mainly in terms of link distance, compared probe excited circular ring above reflector and monopole antenna. The path loss used to determine service range is modelled by two-ray model. The calculation and experimental results are very useful for design and evaluation performance of WLAN bridge systems. ©2005 IEEE.
Keywords: Path loss; Performance evaluation; Probe excited circular ring above reflector